Optimisation of recombinant TNFα production in Escherichia coli using GFP fusions and flow cytometry - Zulkifly, Nurul Asma Hasliza; Selas Castiñeiras, Tania; Overton, Tim W. (Frontiers in Bioengineering and Biotechnology, 2023)
Escherichia coli is commonly used industrially to manufacture recombinant proteins for biopharmaceutical applications, as well as in academic and industrial settings for R&D purposes. Optimisation of recombinant protein production remains problematic as many proteins are difficult to make, and process conditions must be optimised for each individual protein. An approach to accelerate process development is the use of a green fluorescent protein (GFP) fusions, which can be used to rapidly and simply measure the quantity and folding state of the protein of interest. In this study, we used GFP fusions to optimise production of recombinant human protein tumour necrosis factor (rhTNFα) using a T7 expression system. Flow cytometry was used to measure fluorescence and cell viability on a single cell level to determine culture heterogeneity. Fluorescence measurements were found to be comparable to data generated by subcellular fractionation and SDS-PAGE, a far more time-intensive technique. We compared production of rhTNFα-GFP with that of GFP alone to determine the impact of rhTNFα on expression levels. Optimised shakeflask conditions were then transferred to fed-batch high cell density bioreactor cultures. Finally, the expression of GFP from a paraBAD expression vector was compared to the T7 system. We highlight the utility of GFP fusions and flow cytometry for rapid process development.